New updates in the world of hepatitis C virus infected organ transplantation. Issue 4 (August 2020) - Prakash, Katya; Aslam, Saima
Abstract : Purpose of review: With the advent of direct acting antiviral (DAA) therapy, the use of organs from hepatitis C virus infected (HCV+) donors is gaining more traction. In this review, we aim to: provide an overview of recent literature that supports the use of HCV+ organs, outline ongoing challenges to the use of these organs, and highlight the areas within this field where active investigation is ongoing. Recent findings: The present review describes clinical outcomes related to the transplantation of both HCV+ nonviremic and viremic organs and the distinction between hepatic and nonhepatic transplants. It also discusses the current debate pertaining to the ideal treatment strategy for donor-derived HCV infection, that is pre-emptive therapy versus prophylaxis therapy. Summary: Data suggest that the use of HCV+ organs is an effective and relatively well tolerated strategy to combat the organ scarcity. However, clinicians must be vigilant to a signal of increased inflammation as HCV+ organ transplantation becomes more universal. Recent studies suggest that shorter courses of DAA may sufficiently treat donor-derived HCV infection, however the best treatment approach to minimize risk, cost, and toxicity is still under investigation.